PENGARUH SUHU DAN LAMA PENGERINGAN TERHADAP KARAKTERISTIK KOMPOSIT PLASTIK BIODEGRADABLE DARI PATI KULIT SINGKONG DAN KITOSAN - Heni Epriyanti, Ni Made; Admadi H, Bambang; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 1 (2016): Maret, 2016)
The aims of this research were: 1) to determine the effect of drying temperature and drying time to the characteristics of biodegradable composite plastic from cassava skin starch and chitosan, 2) to obtain the best of drying temperature and drying time to produce the best characteristic of biodegradable composite plastic from cassava skin starch and chitosan. This research was performed using factorial randomize block design. The first factor was 3 levels of drying temperature in 50 o C, 60 o C, and 70 o C. The second factor was the 3 levels of drying time in 4, 5, and 6 hours. The ingredients to produce the main ingredients of cassava skin starch were aquadest; chitosan; 3.5%:44%, and 1.5%:50% of vinegar solutions; and 1% of glycerol. The best result which had 1.04 MPa of tensile strength value, elongation of 54.99%, modulus young of 0.019 MPa, biodegradability of 51.18% with porous morphology and brownish flocks was obtained from 50 o C and 6 hours of drying temperature and drying time, respectively. Keywords: Biodegradation, cassava skin, plastic
Keywords: 84